Let's pluck the daisy: dissection as a tool to explore the diversity of Asteraceae capitula - Fu, Lin (2023)
Asteraceae, the daisy family, are one of the most diverse families of angiosperms and are predominant in many ecosystems, including grasslands, deserts, savannas and high-elevation mountains. They are characterized by a peculiar inflorescence, the capitulum, which mimics a flower, but is actually made up of many tightly grouped florets. The capitulum is considered a key character underpinning the impressive evolutionary success of the family, and it plays a pivotal role in the economic importance of the family, given that many species are cultivated for their capitulum for agricultural and horticultural purposes. However, to date, there is still no comprehensive understanding of the extent of the morphological diversity of capitula across lineages of Asteraceae. This is mainly due to a lack of appropriate tools for describing such a complex and condensed structure. To address the problem, we present a protocol for characterizing the full diversity of capitula from any lineage of Asteraceae. This involves making a whole dissection of a capitulum from fresh material; it is simple and cost-effective and requires relatively easy-to-transport equipment meaning that it can be done during fieldwork.